Tandem Queue and Its Applications in the Production of Bi-layer Tablets - Thapa, Ritu Basnet; Ghimire, Sushil; Ghimire, Ram Prasad (Journal of Nepal Mathematical Society, 2024)
Production of bi-layer tablets involves the concept of tandem queue. Tandem queue is a series of queues in which the output of one queue becomes the input to the next queue. In this paper, two tandem queues are employed. Each queue has heterogeneous mean arrival time and service time. These two queues merge into one finite capacity queue in the production process of the bi-layer tablets. The study investigates various performance measures of the queueing model. Mathematical models and simulations are utilized to evaluate system performance under different scenarios.